2011
DOI: 10.1308/147870811x13137608455334
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sterile versus non-sterile tourniquets on microbiological colonisation in lower limb surgery

Abstract: INTRODUCTION Surgical tourniquets are commonplace in lower limb surgery. Several studies have shown that tourniquets can be a potential source of microbial contamination but have not compared the use of sterile versus non-sterile tourniquets in the same procedures. METHODS Patients undergoing elective orthopaedic lower limb surgery were randomised prospectively to use of non-sterile pneumatic tourniquet or sterile elastic exsanguination tourniquet (S-MART™, OHK Medical Devices, Haifa, Israel). Samples were tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…The use of pneumatic tourniquets in joint arthroplasty is now predominantly part of the standard procedure, as it benefits surgeons by maintaining a bloodless field, improving the visualization of important structures, strengthening the bone cement interface, and expediting the procedure [20]. However, recent studies have shown that reusable tourniquets are indeed contaminated and have postulated their potential role in the development of surgical site infections [8,21-22].…”
Section: Discussionmentioning
confidence: 99%
“…The use of pneumatic tourniquets in joint arthroplasty is now predominantly part of the standard procedure, as it benefits surgeons by maintaining a bloodless field, improving the visualization of important structures, strengthening the bone cement interface, and expediting the procedure [20]. However, recent studies have shown that reusable tourniquets are indeed contaminated and have postulated their potential role in the development of surgical site infections [8,21-22].…”
Section: Discussionmentioning
confidence: 99%
“…It is simple, easy to apply by a single person, and because it acts as an exsanguinator, sterile stockinet, and tourniquet all in one, it reduces the amount of equipment required and improves efficiency. Thompson et al (2011) found in a study of 34 pneumatic tourniquets that 68% were contaminated with bacteria and, thus, could be a source of infection of the surgical site. The sterility of the SRT negates this risk.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have shown that pneumatic tourniquets can carry bacterial flora composed mainly of coagulase-negative staphylococci [9,10]. However, this is a low-pathogenic strain and the tourniquet can be sterilized if necessary.…”
Section: Discussionmentioning
confidence: 99%